Real-life indications to ivabradine treatment for heart rate optimization in patients with chronic systolic heart failure. Issue 7 (July 2018) - Tondi, Lara; Fragasso, Gabriele; Spoladore, Roberto; Pinto, Giuseppe; Gemma, Marco; Slavich, Massimo; Godino, Cosmo; Salerno, Anna; Montanaro, Claudia; Margonato, Alberto
Abstract : N/A: Ivabradine is a selective and specific inhibitor of I f current. With its pure negative chronotropic action, it is recommended by European Society of Cardiology and American College of Cardiology/American Heart Association guidelines in symptomatic heart failure patients (NYHA ≥ 2) with ejection fraction 35% or less, sinus rhythm and heart rate (HR) at least 70 bpm, despite maximally titrated β-blocker therapy. Data supporting this indication mainly derive from the SHIFT study, in which ivabradine reduced the combined endpoint of mortality and hospitalization, despite the fact that only 26% of patients enrolled were on optimal β-blocker doses. The aim of the present analysis is to establish the real-life eligibility for ivabradine in a population of patients with systolic heart failure, regularly attending a single heart failure clinic and treated according to guideline-directed medical therapy (GDMT). The clinical cards of 308 patients with heart failure with reduced ejection fraction (HFrEF) through a 68-month period of observation were retrospectively analyzed. GDMT, including β-blocker up-titration to maximal tolerated dose, was implemented during consecutive visits at variable intervals. Demographic, clinical and echocardiographic data were collected at each visit, together with 12-leads ECG and N-terminal pro–B-type natriuretic peptide levels. Out of 308 analyzed HFrEF patients, 220 (71%) were on effective β-blocker therapy, up-titrated to effective/maximal tolerated dose (55 ± 28% of maximal dose) (HR 67 ± 10 bpm). Among the remaining 88 patients, 10 (3.2%) were on maximally tolerated β blocker and ivabradine; 21 patients (6.8%), despite being on maximal tolerated β-blocker dose, had still HR ≥70 bpm, ejection fraction 35% or less and were symptomatic NYHA ≥2, being therefore eligible for ivabradine treatment. The remaining 57 (18%) patients were not on β blocker due to either intolerance or major contraindications. Among them, 13 (4%) were taking ivabradine alone. Of the final 44 (14%) patients, 27 (9%) showed an inadequate HR control (74 ± 6 bpm). Of these, only eight (3%) patients resulted to be eligible for ivabradine introduction according to HR and ejection fraction parameters. Overall ivabradine was indicated in 52 patients (16.8%) out of 308 enrolled. In conclusion, in a carefully managed population of patients with moderate and stable HFrEF, in which optimal GDMT is properly attained, indication to ivabradine treatment is around 17%.